Antithrombotic Potential of Tormentil Extract in Animal Models - Marcinczyk, Natalia; Jarmoc, Dominika; Leszczynska, Agnieszka; Zakrzeska, Agnieszka; Kramkowski, Karol; Strawa, Jakub; Gromotowicz-Poplawska, Anna; Chabielska, Ewa; Tomczyk, Michal (Frontiers in Pharmacology, 2017)
Potentilla species that have been investigated so far display pharmacological activity mainly due to the presence of polyphenols. Recently, it was shown that polyphenol-rich extract from rhizome of Potentilla erecta (tormentil extract) affects the metabolism of arachidonic acid (AA) and exerts both anti-inflammatory and anti-oxidant activities, suggesting a possible effect on thrombosis. Accordingly, the aim of the study was to evaluate the effect of tormentil extract on haemostasis in a rat model of thrombosis. Lyophilized water-methanol extract from Potentilla erecta rhizome was administrated per os for 14 days in doses of 100, 200 and 400 mg/kg in a volume of 2 mL/kg in a 5% water solution of gummi arabici (VEH). In the in vivo experiment an electrically induced carotid artery thrombosis model with blood flow monitoring was used in Wistar rats. Collected blood samples were analyzed ex vivo functionally and biochemically for changes in haemostatis. Tormentil extract (400 mg/kg) significantly decreased thrombus weight and prolonged the time to carotid artery occlusion and bleeding time without changes in the blood pressure. In the ex vivo experiment tormentil extract (400 mg/kg) reduced thromboxane production and decreased t-PA activity, while total t-PA concentration, as well as total PAI-1 concentration and PAI-1 activity remained unchanged. Furthermore, tormentil extract (400 mg/kg) decreased bradykinin concentration and shortened the time to reach maximal optical density during fibrin generation. Prothrombin time (PT), activated partial thromboplastin time (APTT), QUICK index, fibrinogen level, and collagen-induced aggregation remained unchanged. To investigate the involvement of platelets in the antithrombotic effect of tormentil, the extract was administrated per os for two days to mice and irreversible platelets activation after ferric chloride induced thrombosis was evaluated under intravital conditions using confocal microscopy system. In this model tormentil extract (400 mg/kg) significantly reduced platelet activation at the same extent as acetylsalicylic acid (ASA). Taken together, we have shown for the first time that tormentil extract inhibits arterial thrombosis in platelet- and endothelial-dependent mechanisms without hemodynamic changes. Further studies on the detailed mechanism of action of tormentil extract towards fibrinolysis and the kinin system should be carried out.